Research of RBF neural network PID control algorithm for longitudinal channel control of small UAV - Shichao Wang; Baokui Li; Qingbo Geng (2013 10th IEEE International Conference on Control and Automation (ICCA), 2013)
An intelligent PID controller based on RBF neural network was designed for longitudinal attitude control of a small unmanned aerial vehicle (UAV) according to the feature of complexity and nonlinear; RBF neural network is used to real-time update the PID parameters on line by its learning function for achieving the longitudinal channel control of the UAV; Simulation results show that the design of the RBF neural network PID controller has better control performance and it better satisfies the requirements of the longitudinal channel flight control of small UAV.